The Normalization of Domestic Violence in Bangladesh: Analysing through the Lens of Social Learning Theory - Rahman, Farzana; Sakib, A B M Najmus (Social Science Review, 2023)
The study focuses on the gender-biased socialization process inside the patriarchal social system, which institutionalizes domestic violence against women and transmits it from generation to generation. A culture of normalization contributes to the increased incidence of domestic violence against women, which is socially acceptable despite the fact that it affects women. Domestic violence was predicted to decrease annually in Bangladesh due to improved literacy rates, women’s empowerment and participation, and economic prosperity, among other factors. Despite these assumptions, the frequency of violence continues to rise. This qualitative study analyses how sociocultural factors influence domestic violence’s acceptance in Bangladeshi society. Additionally, it has an intergenerational effect, which has been examined through Albert Bandura’s social learning theory. The researchers conducted extensive semi-structured interviews with participants to understand the issue as a social phenomenon. The paper concludes with a few ideas for a long-term policy to eradicate the root causes of domestic violence against women in society. Social Science Review, Vol. 39(1), June 2022 Page 141-164